The refugee – a literary topos - Wolting, Monika (Porównania, 2022)
In the article I deal with the depiction of the fate of refugees in German-language literature. It is evident that the refugee figure is a link between exile, migration and displacement literature. It is productive for the literary debate to highlight figures and spaces of flight, because this can lead to the abolition of the marginal position of migration literature within contemporary literature.